PHYSICAL MODEL OF THE ORBITAL MOVEMENT OF THE JUPITER SATELLITE SINOPE - Ostrovskiy, N. V. (Одеські астрономічні публікації, 2017)
The physical models of orbital movement of heavenly body have limited application. On the one hand, it is very difficult to take into account all effects of gravitational interaction in complex systems. Therefore the physical models cannot compete on accuracy of calculation of ephemeris with statistical models. On the other hand, the known equation of world gravitation of Newton strictly corresponds only to gravitational interaction of two bodies. With its use it is impossible, for example, to explain a movement of the Moon around the Earth, as the Moon is in sphere of Sun gravitation. The similar situation exists and in case of the external satellites of Jupiter: Pasiphe and Sinope. In the given work is used the original equation for the description of gravitational interaction in system of many bodies (for system of two bodies it is converted in the Newton equation), that eliminates the known contradiction.